Research regarding physical fitness characteristics viewed over a long period of time targeting junior tennis players - Umebayashi, K.; Imanishi, T.; Suda, K. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: It has been a long time since the physical fitness improvement plan intending to strengthen Japan`s tennis players started. We have been implementing physical fitness measurement of junior players in the Japanese tennis player training project since 2001. The purpose of this research is to analyze the results of physical fitness measurements of junior tennis players which we implemented from 2001 to 2012, understand the characteristics thereof, and suggest a directionality for future physical training. Methods: The junior tennis players who were the subjects of measurement were 139 players from age 12 to 16 who had achieved good results in domestic and overseas matches and been designated in each region as strengthened. The items measured were height, weight, grip strength, standing long jump, sit-ups, long sitting body anteflexion, round-trip running, 5-direction run, shuttle stamina, and medicine ball throwing. The method of analysis was aggregating the physical fitness measurement results by gender and comparing them by year (2001 group, 2005 group, and 2012 group). Furthermore, we converted the measurement data to a standard score (H store) and conducted a comparison on relative physical fitness points to consider the characteristics of each year. Results and Discussion: The comprehensive physical fitness points were significantly lower in the 2012 group compared to the 2001 and 2005 groups in both boys and girls. Among these, the most remarkable differences were found in sit-ups, grip strength, and medicine ball throwing--items which require muscle strength. On the other hand, in the girls the tests of physique, endurance running (shuttle stamina), sprinting ability (running back and forth on the court) tended to be better in the 2012 group. No difference was observed in sprinting ability among the boys. These facts suggest the possibility that recent Japanese junior tennis players have adopted a playing style which focuses on sprinting ability and footwork and training focusing on these as well in comparison to past junior tennis players. The results suggest that in the future it will be necessary to maintain this play style as a foundation while making training plans which emphasize muscle strength and powerrelated physical fitness building.